Faktor-Faktor yang Mempengaruhi Perilaku Konsumen Dalam Memilih Pegadaian Syariah di Kota Banjarmasin - MUBARAK, ZAKI; WINDASARI, INDRIANI (Islamic Economics and Business Faculty of UIN Antasari, 2013)
This study intends to find out if factors including product, promotion, price, place, and service have affected consumers behavior in choosing syariah pawn shop (pegadaian syariah). The regression analysis results show that those factors have affected consumer decision making at 63.9%. UsingF test, all of those variables simultaneously have affected consumers decision in choosingsyariah pawn shop. Furthermore, using t test, only some variables including product, price, and place that partially have affected the consumers behavior, but, promotion and service have not affected it. The data analysis also indicates that price is the most dominant variables that affected consumers in choosing Syariah pawn shop.